I will be especially very careful - Child, Lauren; Starkey, Anna.; Tiger Aspect Productions (New York : Dial Books for Young Readers, 2009)
When Lola's best friend Lotta gets a fluffy new coat, Lola borrows it and proceeds to almost ruin and lose the fluffy, pristine garment while running errands.
2.8
K-3.
K-3
Keywords: Charlie (Fictitious character : Child) -- Juvenile fiction; Coats -- Juvenile fiction; Lola (Fictitious character : Child) -- Juvenile fiction; Charlie (Fictitious character : Child) -- Fiction; Coats -- Fiction; Lola (Fictitious character : Child) -- Fiction; Charlie (Fictional character : Child) -- Fiction; Coats -- Fiction; Lola (Fictional character : Child) -- Fiction; Picture books for children